ANALISA FAKTOR PENGARUH PEMBENTUKAN KELEMBAGAAN COMPUTER EMERGENCY RESPONSE TEAM (CERT) NASIONAL DENGAN MENGGUNAKAN ANALISIS PROSPEKTIF - Setiawan, Ahmad Budi (Masyarakat Telematika Dan Informasi : Jurnal Penelitian Teknologi Informasi dan Komunikasi, 2011)
Along with the increasing volume of information security attacks in Indonesia, it takes the Information Secur!ty Response Team to deal with the threats. Related matter, Carnegie Mellon University established the Computer Emergency Response Team (CERT), which is currently spread throughout the world. Currently in Indonesia have had two information security incident response team, which is ID-SIRTII and CERT ID. Both teams did not have a coordinated response and a efektip command line. Thus the required institutional Information Security Response Team effective in Indonesia. In this research examined the factors that influence the institutional formation of the Information Security Response Team. This study was carried out qualitative and analytical methods are discussed in perspective analysis. Results from this study are the factors that influence the institutional of Information Security Response Team.